UPAYA PELESTARIAN RUMAH ADAT KARO MELALUI RUPA RAGAM HIAS DI SUMATRA UTARA: Rumah adat karo - Seriwati Ginting; Heddy Heriyadi; Sri Bina Carolina (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2021)
The Karo traditional house is one of the cultural heritages in North Sumatra Province. The Karo tribe, is one of the largest tribes. Karo Regency is located on a plateau called Tanah Karo, with a cool climate. It has its own language called cakap Karo, and has Karo script. An area of ??2,127.25 square kilometers with a population of 959,000. The Karo tribe comes with simplicity manifested in an attractive and magnificent traditional house. The Karo traditional house is called Siwalauh Jabu (eight families live in it) The process and life of its inhabitants are arranged in a way. Decorative ornaments in traditional Karo houses are called